Whole-Body MRI and Ethnic Differences in Adipose Tissue and Skeletal Muscle Distribution in Overweight Black and White Adolescent Boys. (20th June 2011) - Lee, SoJung; Kim, YoonMyung; Kuk, Jennifer L.; Boada, Fernando E.; Arslanian, Silva
Abstract : It is unclear whether ethnic differences exist in adipose tissue (AT) and skeletal muscle (SM) distribution in black and white youth. Investigation into the pattern of AT and SM distribution in black versus white youth may provide insight into the previously reported health disparities between these ethnicities. Therefore, we examined total and regional AT and SM in overweight black and white boys. The study sample included overweight black (n = 19 ) and white (n = 21 ) boys (11–18 yr, BMI ≥ 85th) whose body composition was evaluated using whole-body MRI. Despite similar age, Tanner stage, and BMI, black boys had significantly (P < .05 ) less visceral AT than white boys and more (P < .05 ) total and lower-body subcutaneous AT (SAT) in both absolute (kg) and relative (%) terms. There was a main effect (P < .05 ) of ethnicity on the relationship between total and regional AT, such that for a given amount of total body AT (kg), black boys had a greater (P < .05 ) lower-body SAT and less visceral AT than their white peers. For a given amount of total SM, black boys had more (P < .05 ) SM in the thigh. Compared with overweight white boys, overweight black boys have less visceral fat, more subcutaneous fat, and more thigh skeletal muscle.